Paola Cortellesi’s Magic Spell: Domestic Violence and Fairy-Tale Subversion in C’è ancora domani (2023) - Sottilotta, Elena Emma (Quaderni d'Italianistica)

(untitled) (Iter Press, 2024)
Paola Cortellesi’s C’è ancora domani (2023) portrays happiness and misery within the confines of domestic life, giving prominence to the themes of gender-based violence and women’s hope for redemption. Drawing on the tropes of neorealism, the film is centred on Delia, a working-class woman who lives under the brutal oppression of a despotic husband, on the eve of the 1946 institutional referendum that inaugurated the birth of the Italian Republic. Initially a submissive Cinderella-like character, Delia toils inside and outside the domestic walls to support her family despite relentless beatings and humiliations. By combining a close reading of key scenes with an exploration of the film’s soundscape and its reception, this essay argues that C’è ancora domani can be interpreted as a subversive fairy-tale film. The director herself drew a connection between the film and fairy tales in a speech she delivered at the Luiss Guido Carli University in Rome in January 2024, which sparked a heated debate in the Italian press on the sexist nature of classic fairy tales. The film radically questions clichéd representations of female roles, repeatedly trumping audience expectations with its revolutionary edge. This subversive power, infused with an underlying longing for hope, aligns with the transformative spirit of the fairy-tale genre. Throughout the film, Cortellesi juxtaposes scenes of domestic violence with moments of ironic levity, accentuating the chasm between Delia’s grim reality and her dreams of escape. By putting the film into conversation with fairy-tale studies, this essay ultimately interprets C’è ancora domani as a work of art that boldly subverts women’s traditional roles within the domestic space.